THE USE OF CODE MIXING BY FOREIGN REFUGEES IN MULTILINGUAL ENVIRONMENT OF MAKASSAR CITY TOWARDS ENGLISH LANGUAGE TEACHING IN INDONESIA - Andi Indah Permatasari Hasbi; Amirullah Abduh; Muhammad Arham Basri; Muh Tahir (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
This study aimed to explore how code mixing is used in multilingual interactions among foreign refugees and how it impacts English language teaching in Indonesia. In Makassar, refugees experienced legal uncertainty and integration challenges, particularly in acquiring new languages. Code mixing, the practice of combining native languages with Indonesian or English, served as a means of adaptation, identity preservation, and communication, all viewed through a sociolinguistic lens. Using a descriptive qualitative approach, the study focused on refugees from Sri Lanka, Iran, and Afghanistan, gathering data through observations, interviews, and document analysis. Triangulation ensured data validity, while thematic analysis uncovered patterns related to language use, identity, social integration, and power dynamics. The results revealed that refugees’ language learning is strongly shaped by the sociolinguistic environment. Their language choices often reflected the local context and the languages spoken around them. Code mixing emerged as a practical communication strategy, with English serving as a key tool in bridging language barriers. Sociolinguistic factors greatly influenced how refugees acquired new languages, and these insights can help improve language education programs to better support refugee integration. Code mixing proved essential in helping refugees navigate multilingual interactions while adapting to their new cultural and linguistic surroundings. The combined use of English and code mixing facilitated communication, expressed personal identity, and supported social integration. The study also recommended that Indonesia adopt some of the refugees’ language learning strategies, such as peer learning, language exchange, contextual learning, and encouraging a tolerance for making mistakes. These methods could enhance English proficiency among Indonesians, promote multilingualism, and inspire further research into language acquisition